The plugged-in professor : tips and techniques for teaching with social media - Ferris, Sharmila Pixy; Wilder, Hilary Anne (Chandos social media series., 2013)
New technologies are transforming the way students work. The Plugged in Professor provides a timely and exceptional resource for using social media and other new technologies to help college students meet both general and discipline-specific objectives. The title covers techniques built around well-known social networking technologies, as well as other emerging technologies such as mobile phone and tablet apps. With a practical focus and reader-friendly format, this book shows educators how to apply techniques in each technology, and includes clear student learning objectives and step-by-step directions.